Doenças de psittaciformes na região central do Rio Grande do Sul - Murer, Laurete (2017)
This thesis aimed to study the diseases of Psittaciformes diagnosed at the Center for Studies and Research in Wild Animals of the Federal University of Santa Maria (NEPAS / UFSM). For the preparation of this paper, the records of the 495 necropsies of wild animals carried out from January 2013 to December 2016 were examined, in addition to the results of the investigation of the Salmonella spp. presence carried out in clinical care to two psittacids breeders. The main macroscopic alterations observed at necropsies were grouped by systems, analyzed through a descriptive meta-analysis, where it was verified that the digestive system presented the highest number of alterations (29.4%), followed by the respiratory system (18.6 %), cardiovascular (14.6%), musculoskeletal (12.6%) and presence of parasites or fungi (8.4%). In an expressive number of cases (16.5%) it was not possible to identify the lesions due to the advanced stage of decomposition of the cadavers, or because they were macroscopic alterations that would not lead the animal to death. During the study period, two cases of greater relevance appeared, for which the investigation of the causa mortis was sequenced, with the accomplishment of histopathological and molecular tests that resulted in two reports: the first report in Brazil of the clade C avipoxvirus presence and another, the first report in Brazil of the herpesvirus of the Psittacidae type 3, both in captive Psittaciformes. Thus, this study resulted in four scientific studies: (1) Descriptive meta-analysis of the pathological alterations of wild birds and mammals diagnosed in the central region of Rio Grande do Sul: 495 cases; (2) Identification and phylogenetic analysis of clade C avipoxvirus in a fowlpox outbreak in exotic Psittaciformes in Southern Brazil; (3) Psittacid herpesvirus 3 infection in rose-ringed parakeets (Psittacula krameri) in Southern Brazil and (4) Investigation of Salmonella spp. in exotic and native Psittaciformes kept in captivity in the central region of Rio Grande do Sul. This work will contribute with clinical and pathologists veterinarians in the diagnosis of diseases present in the central region of Rio Grande do Sul.